The influence of the educational and family environment on the preschool - Călin, Mariana Floricica; Rus, Mihaela; Sandu, Mihaela Luminița (Technium Social Sciences Journal, 2021)
Johann Wolfgang von Goethe says behavior is "the mirror in which each reflects his image." This is also visible to preschoolers who through their innocence and sincerity exhibit behavioral differences in the family and in the educational institution. The creativity and imagination of the children goes beyond the imaginary lines of reason and the physical contour of this drawing, having a story behind the visible stories of the craft that it carries out.